If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xy(5x + -3) = 0 Reorder the terms: 3xy(-3 + 5x) = 0 (-3 * 3xy + 5x * 3xy) = 0 (-9xy + 15x2y) = 0 Solving -9xy + 15x2y = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3xy'. 3xy(-3 + 5x) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'xy' equal to zero and attempt to solve: Simplifying xy = 0 Solving xy = 0 Move all terms containing x to the left, all other terms to the right. Simplifying xy = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-3 + 5x)' equal to zero and attempt to solve: Simplifying -3 + 5x = 0 Solving -3 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 0 + 3 5x = 0 + 3 Combine like terms: 0 + 3 = 3 5x = 3 Divide each side by '5'. x = 0.6 Simplifying x = 0.6Solution
x = {0.6}
| 12x/78x | | 2x-(4+x)=7 | | 2x+x+6x=153 | | 5-3x+2=8-3x | | 2x-4*(x-4)=2y | | 9m*(-3)= | | x^3-45x^2+10000=0 | | 4x+3-x=-6x-7 | | 7x(3+b)=28 | | 2e-6=0 | | 293X-1= | | 1/3x5/6x9/10 | | X-5=9+X | | 7g-11=24 | | (5.4/x)=(.5^6) | | 12+15y-y=12 | | (k^2)-5k-10=0 | | (k^2)-5k+10=0 | | (k^2)-5k-4=0 | | (k^2)-5k+4=0 | | (2-3i)*(x+yi)=5-i | | 4x=6-1 | | 2x+3x-2x= | | 4(m-2)-8+2m=6(m+5) | | Ax+4y+4x+ay= | | x=1.04*y+6.18 | | 2x+3y+1z=51.4 | | X^3/3=65 | | X/3=65 | | 6(y-5)=4(y+2) | | 5y=10x+2 | | x*2-8=8 |